Pengembangan Booklet Penyakit Menular Seksual pada Usia Remaja Sekolah untuk SMA - Wicaksana, Ervan Johan; Lukman, Aprizal (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2020)
This research aims to produce a booklet of sexually transmitted diseases in school adolescents. Based on data from the Sexual Transmitted Disease Service Report of the Jambi City Health Office in 2018 there were 644 cases of sexually transmitted diseases in the city of Jambi, and 18 of them occurred in their teens. An interesting learning media is needed to help teachers explain the material about sexually transmitted diseases. This type of research is research and development using the ADDIE development model. The analysis phase consists of needs analysis and material analysis. The Design (design) consists of the initial design of the product to the making of a prototype. The Development Phase consists of validation of material and media experts as well as trials conducted on Biology teachers, small group trials and large group trials. The implementation phase is carried out in class XI IPA1 of SMAN 10 Jambi City using one group pretest-posttest design. The evaluation phase consists of the suggestions of the validator, the teacher and the test subject. The result of the material expert validator, booklet with a percentage of 95% (very good). The final results of the media expert validator of the booklet with a percentage of 93.33% (very good). The results of the Biology teacher's perception of the sexually transmitted diseases booklet with a percentage of 92.30% (very good). The results of small group and large group trials of students are 88.05% and 90.05% in the excellent category. Pre-test and post-test results were analyzed using N-gain and obtained an average of 0.84 in the